1996
DOI: 10.1046/j.1365-2826.1996.04411.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Oxytocin Release in the Paraventricular Nucleus in the Control of Maternal Behaviour in the Sheep

Abstract: Oxytocin (OT) release within the brain is thought to play a major role in inducing maternal behaviour in a number of mammalian species but little is known about the sites of release which are important in this respect. We have investigated whether the paraventricular nucleus of the hypothalamus (PVN) is a site of OT action on maternal behaviour in the sheep. In vivo microdialysis and retrodialysis was used to determine whether OT is released in the region of the PVN during the post-partum induction of maternal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
0
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 113 publications
(75 citation statements)
references
References 8 publications
2
72
0
1
Order By: Relevance
“…Because the paraventricular nucleus is the main source of OT release into the brain, upgrading autoreceptors on OT-containing neurons serves to promote further OT release throughout the brain. Certainly, during parturition, levels of OT in cerebrospinal fluid (CSF) increase to 400 pg ml K1 and reach all areas of the brain including the OB, where receptors are upregulated during pregnancy (da Costa et al 1996). Since there are no OT terminals in the OB, this humoral transport serves an important function in the context of receptor terminal mismatch (Yu et al 1996a,b).…”
Section: Precocial Mammals: Maternal Bondingmentioning
confidence: 99%
“…Because the paraventricular nucleus is the main source of OT release into the brain, upgrading autoreceptors on OT-containing neurons serves to promote further OT release throughout the brain. Certainly, during parturition, levels of OT in cerebrospinal fluid (CSF) increase to 400 pg ml K1 and reach all areas of the brain including the OB, where receptors are upregulated during pregnancy (da Costa et al 1996). Since there are no OT terminals in the OB, this humoral transport serves an important function in the context of receptor terminal mismatch (Yu et al 1996a,b).…”
Section: Precocial Mammals: Maternal Bondingmentioning
confidence: 99%
“…Indeed, in vivo microdialysis revealed that OT is released in the PVN at lambing as well as during artificial VCS. Furthermore, retrodialysis infusion of OT stimulates maternal behavior in nonpregnant animals primed with a steroid treatment (Da Costa, Guevara-Guzman, Ohkura, Goode, & Kendrick, 1996). However, OT release also occurs in the BNST, MPOA, and the olfactory bulb during parturition and/or following VCS (Da Costa et al, 1996;Kendrick, Keverne, Hinton, & Goode, 1992a).…”
Section: Neural Structures and Neurochemical Processesmentioning
confidence: 99%
“…Presumably OT release at some of the other targets of the PVN mediates positive maternal responses, but this remains to be tested. Strikingly, OT infusion into the PVN itself induces full maternal responses in steroid primed ewes (Da Costa et al, 1996). This is thought to be due an autocrine loop of OT-induced OT release at all terminal target sites of the oxytocinergic PVN neurons, because these neu- , and A6) from the brain stem.…”
Section: Maternal Behavior In Rats and Sheepmentioning
confidence: 97%
“…Parturition or vaginocervical stimulation induces release of the neuropeptide OT in several brain areas in both sheep and rats, and this release appears to coordinate the onset of maternal behavior with birth (Kendrick et al, 1986(Kendrick et al, , 1988(Kendrick et al, , 1997Kendrick and Keverne, 1992;Levy et al, 1992;Neumann et al, 1993;Da Costa et al, 1996). Intracerebroventricular (ICV) infusion of OT in steroid primed nonpregnant animals of both species rapidly induces maternal responses (Pedersen et al, 1982;Kendrick et al, 1987).…”
Section: Maternal Behavior In Rats and Sheepmentioning
confidence: 99%
See 1 more Smart Citation